Political economy of climate change adaptation: Loss of habitat and rising inequality - Yasmine van der Straten; Enrico Perotti; Frederick van der Ploeg (Tinbergen Institute, 2024)
We study the evolution of voter support for climate policies aimed at containing the effect of climate risk, as weather conditions worsens at a time of rising economic inequality. Households differ in age, beliefs and income, and the scale of intervention to preserve habitable land reflects the preference of the majority coalition. Economic polarization tightens conditions for more households, while rising climate risk increases support for public adaptation. If beliefs on attainable impact are not too dispersed, an initially coalition of young and old pessimists might tip towards a coalition of old optimists and young pessimists, leading to a jump in support for public action.A steady rise in inequality may ultimately induce a second political tipping point, towards a coalition of the low-income old and young pessimists, although the effects on public adaptation are weaker. Public intervention is undermined by pessimism about the efficacy of public adaptation and the "tragedy of the horizon" effect, as voters only partially internalize benefits for future generations. This prevents public adaptation from converging to the long-term social optimum even when political support is highest.
Keywords: D63; H23; Q54; Q58; 330; Climate Change Adaptation; Economic Inequality; Tragedy of the Horizon; Political Tipping Points